Operator Approach in the Problem of Radiation by a System of Slots in a Plane Waveguide - Kaliberda, M. E.; Pogarsky, S. A. (Видавничий дім «Академперіодика», 2012)
The problem of determining the characteristics of bounded element and semiinfinite system of slots in one wall of a plane waveguide is solved by the operator approach. The mutual influence of slots through free space is taken into consideration. The directional patterns of waveguide eigenwaves radiated field are presented. Our results have been compared with those obtained by the method of discrete singularities.